MR imaging biomarkers in HCC: outcomes correlation in liver transplant listed patients. Issue 4 (13th February 2023) - Wibulpolprasert, Pornphan; Agopian, Vatche; Dumronggittigule, Wethit; Lee, Yong Seok; Yuen, Alexander; Raman, Steven S.; Markovic, Daniela; Lu, David S.
Abstract: Purpose: To determine hepatocellular carcinoma (HCC) magnetic resonance imaging (MRI) biomarkers that enable the prediction of delisting from tumor progression versus successful transplantation in patients listed for orthotopic liver transplantation (OLT). Methods: With IRB approval and HIPPA compliance, patients with HCC awaiting OLT who were delisted due to HCC progression from 2006 to 2015 were identified. Patients with adequate MR images for review were subsequently matched with a cohort of patients successfully bridged to OLT in the same time period. Matching considered the tumor stage and the dominant treatment strategy adopted to bridge the patient to OLT. Potential MRI features were evaluated by univariable and multivariable analysis using a conditional logistic model. Results: There were 53 patients included in each cohort. On uni‐variable analysis, significant unfavorable MR imaging features included T2 hyperintensity (odds ratio [OR], 19.0), infiltrative border (OR, 7.50), lobulated shape (OR, 4.5), T1 hypointensity (OR, 3.0), heterogeneous arterial enhancement (OR, 7.0), and corona venous enhancement (OR, 4.0). A significant favorable MR imaging feature was the presence of intralesional fat (OR = .36). The best multivariable logistic prediction model derived from the above notable features included only T1 and T2 signal intensity, border definition, and absence of intra‐lesional fat as significant variables, with an area under the receiver operating characteristic curve (AUC) of .86 in the prediction of delisting. Conclusion: Select MR imaging features of HCC at presentation before any treatment are significantly associated with the risk of tumor progression regardless of tumor stage and treatment strategy in patients awaiting liver transplantation.